APPLICATION OF THE TEAM GAMES TOURNAMENT (TGT) MODEL TO IMPROVE BASIC MATHEMATICS LEARNING OUTCOMES FOR CIVIL ENGINEERING STUDENTS - Rizky Febriani Pohan; Muhammad Rahman Rambe; Wirna Arifitriana (ALGORITMA: Journal of Mathematics Education, 2022)
The success of students in mastering the subject matter of Basic Mathematics can be seen from the results of learning Basic Mathematics. One of the learning models that can activate students and improve learning outcomes in Basic Mathematics is the Team Games Tournament (TGT) learning model. This study aims to determine the effect of the Team Games Tournament (TGT) learning model on the learning outcomes of Basic Mathematics students of the Civil Engineering Study Program and to prove that the Team Games Tournament (TGT) learning model is able to improve learning outcomes of Basic Mathematics students of the Civil Engineering Study Program. This research was conducted through Classroom Action Research (CAR) with a research sample of 40 people. The design used in this study was a pretest-posttest control group design. Based on the research results obtained, it can be concluded that the results of the t-test hypothesis test indicate that tcount ≥ ttable or 14.6551≥ 2.023. This means that Ho is rejected or Ha is accepted. So that the Team Games Tournament (TGT) learning model affects the learning outcomes of Basic Mathematics students of the Civil Engineering Study Program, Universitas Graha Nusantara Padangsidimpuan. Through the application of the Team Games Tournament (TGT) learning model, it is proven that the learning outcomes of Basic Mathematics students of the Civil Engineering Study Program at Graha Nusantara University Padangsidimpuan increased by 48.75% with a percentage effectiveness of 7.14%.